Renal Autotransplant and Celiac Artery Bypass for Aneurysmal Degeneration Related to Neurofibromatosis Type 1. (August 2019) - Drucker, Natalie A.; Blaibel, Maher F.; Nagaraju, Santosh; Wang, S. Keisin; Goggins, William; Fajardo, Andres
We present a case of an 18-year-old female with neurofibromatosis type 1 who presented with abdominal pain and weight loss secondary to chronic mesenteric ischemia due to celiac axis occlusion and was subsequently found to have multiple visceral artery aneurysms. Of clinical significance, 2 aneurysms of the right renal artery were noted at the hilum, with the larger one having a diameter of 2.4 cm. After initial endovascular treatment with stenting of a concurrent pancreaticoduodenal artery pseudoaneurysm, staged aorto-hepatic bypass and right nephrectomy with renal autotransplantation after back table resection of the aneurysmal segments were successfully completed.